Antiques frame [large type] - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery., 2018)
When her initial successes with her hit reality series are jeopardized by a rival show starring her police chief boyfriend's ex, Brandy finds herself framed for murder while her kooky mom sorts through a rogue's gallery of suspects.